WORK OF A HIGHER EDUCATIONAL INSTITUTION MULTIDISCIPLINARY DEPARTMENT ON THE FORMATION OF PROFESSIONAL COMPETENCES OF FUTURE ELEMENTARY SCHOOL TEACHERS - Gutsu, E. G.; Smirnova, E. I. (Obrazovanie i nauka, 2017)
The aim of the study is to test new approaches to the management of professional and personal development of students of pedagogical university. Methodology and research methods. The theoretical analysis of the following information sources was carried out: psychological, pedagogical and methodological literature on the researched topic; teaching-program documentation and teaching materials (work programs of studying disciplines, textbooks, manuals, collections of tasks, guidelines, etc.); normative documents (Federal State Educational Standards (FSES), General Educational Programs (GEP), curricula, instructional acts, etc.). The methods of modeling and expert evaluation were used. Results and scientific novelty. The features of integrative activities of the multidisciplinary department of pedagogical university for formation of professional competences of future elementary school teachers are revealed. The diagnostics of the competences mastered by pupils at the level of a bachelor degree was carried out during deployment period, carrying out mini-researches and performing of the combined analytic-constructive and diagnostic tasks at lessons. Practical significance. The diagnostic approach to formation of professional competences of future teachers of primary school (undergraduate level) under conditions of multidisciplinary department work may be of interest to teachers of other pedagogical universities and colleges.